2021
DOI: 10.1109/access.2021.3080086
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Tunable ACO Based Fuzzy FOPID Controller for Effective Speed Control of Electric Vehicle

Abstract: The phenomenal growth of the Electric Vehicle (EV) technology demands efficient and intelligent control strategies for the propulsion system. In this work, a novel fuzzy fractional order PID (FOPID) controller using Ant Colony Optimization (ACO) algorithm has been proposed to control EV speed effectively. The controller parameters and the fuzzy logic controller's membership functions are tuned and updated in real-time using the multi-objective ACO technique. The proposed controller's speed tracking performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Derivative control action cannot be utilized alone because this control is efficient only during transient period [30]. The PID controller decreases the time response with less overshoot and most common technique is the control by a great margin.…”
Section: Bldc Motormentioning
confidence: 99%
See 1 more Smart Citation
“…Derivative control action cannot be utilized alone because this control is efficient only during transient period [30]. The PID controller decreases the time response with less overshoot and most common technique is the control by a great margin.…”
Section: Bldc Motormentioning
confidence: 99%
“… computational work than optimization processes, iterative techniques, or simple heuristics. Intrinsically, they are effective methods for optimization processes [33]. Most academic writing on metaheuristics is new, illustrating practical solutions based on computer tests with the systems.…”
Section: Fopid Controller Metaheuristic Optimizationmentioning
confidence: 99%
“…An in-depth analysis of the chopper on simulation model development [2], Controlling chopper operation [3][4][5] according to earth terrain and under specifics requirements such state of charge (SOC) was done using expert systems [4], adaptive neuro fuzzy inference system (ANFIS). A New European Driving Cycle (NEDC) [5][6][7][8] test for testing vehicle performance and emission which is part of the requirement of commercial vehicle can be extended to Electric Vehicle. The expected vehicle result pattern can be followed using simulation model that can have long duration and high speed simulation time such as one developed using anumerical representation utilising Taylor series [9].…”
Section: Introductionmentioning
confidence: 99%
“…The fuzzy self-tuning PID control method of the combined brake of the in-wheel motor-driven electric vehicle was studied. George et al 14 used the ant colony optimization (ACO) algorithm to tune the parameters of the PID controller to effectively control the speed of electric vehicles. Dutta and Nayak 15 reported that brushless DC motors were superior to brushed DC motors.…”
Section: Introductionmentioning
confidence: 99%